Testing the quick meal hypothesis: the effect of pulp on hoarding and seed predation of Hymenaea courbaril by red-rumped agoutis (Dasyprocta leporina) - Guimaraes, P. R.; Kubota, U.; Gomes, B. Z.; Fonseca, R. L.; Bottcher, C.; Galetti, M. (Blackwell Publishing, 2006)
Red-rumped agoutis (Dasyprocta leporina) are important seed dispersers/predators of Neotropical large-seeded plants. Several species of seeds cached by agoutis have an edible reward, in contrast to temperate rodent-dispersed diaspores. The quick meal hypothesis states that the presence of a reward such as edible pulp will enhance the efficiency of rodents as seed disperses by satiating the animal and, consequently, reducing seed predation and enhancing hoarding. In this study, this hypothesis was tested using as the reference system the pulp and seeds of Hymenaea courbaril. Seeds with and without pulp were offered to agoutis and the behaviour of each individual was recorded. Since the probability of predation and hoarding were complementary, we used the probability of predation. The proportion of agoutis that preyed on at least one seed was similar for seeds with (42.8% of individuals) and without (40.0% of individuals) pulp. In agoutis that preyed upon at least one seed, the probability that they killed a seed did not differ between seeds with (0.17 +/- 0.03) and without (0.20 +/- 0.08) pulp. Hence, these results do not support the 'quick meal hypothesis'.
Keywords: Atlantic forest; caching; Caviomorpha; food hoarding; seed predation